If you are orejón, you are noble. Reflections on pre-hispanic Metal earmuffs in the south-central andean area - Sagárnaga M., Jédu A. (2021)
Starting from the ethnohistorical data, the aim is trying to reconstruct which was the use of earmuffs and their meaning in the Inka society. But it also makes use of the iconographic data (reflected in drawings, wooden vases and colonial paintings) as well as the archaeological data (recovered especially in small metal figurines). The only evidence of the Post Tiwanaku Period is provided by the Mollo culture, although the archaeological sample is reduced to just only 4 gold earmuffs. The analysis does not stop there but, in retrospect, tries to observe what happened during the Middle Horizon, basing the observation both on the iconography (mainly ceramic representations) and also on the object itself.